Paper Panda's guide to papercutting - Firchau, Louise (Search Press Limited, 2017)
"This book has Paper Panda's very distinctive stamp on it and begins with a design section which takes the reader through a very personal account of what inspires her, how she works, and how Paper Panda came about. The techniques involved in papercutting are fairly simple and easy to explain, and this is covered through step-by-step demos. There is a design section, taking readers through the design process itself and including numerous examples of Louise's papercut designs. Starting with the themes and subjects that inspire her, it explains how she creates finished artwork suitable for papercutting, followed by how to make the template itself, and how to use the papercut to make cards, framed pictures, and so on. The aim of this section will be not only to provide readers with an insight into Paper Panda's creative world, but also to inform and inspire people to design papercuts for themselves. There are 20 papercut projects in the book; five from Paper Panda herself and five each from three of Paper Panda's design colleagues (Sarah Trumbauer, Louise Dyer and Suzy Taylor -- all accomplished papercutters with online presences). Each project will consist of a template, which will be reproduced full-size at the back of the book, and a finished paper cut, together with some step-by-step instructions. The designs will be simple enough for beginners, though attractive and interesting enough to inspire more advanced paper cutters. The projects themselves will include cards, decorations, and mounted and framed pictures to hang on the wall, all using a variety of colored and patterned papers to show off Paper Panda and friends' distinctive and beautiful designs to their best advantage"--